COMPOSITIONS AND METHODS FOR APPLICATION OVER SKIN - AKTHAKUL, Ariya (2022)
Compositions that contain a volatile agent and can be used to create a thin film on the skin of a subject wherein the volatile agent is capable of transporting out of the film. In one embodiment, the volatile agent is transported out of the composition by convection. In one embodiment, the volatile agent is transported out of the composition by diffusion. A composition for application to skin of a subject, wherein the composition includes a) a bifunctional organopolysiloxane polymer having one unsaturated group and one hydride group; and b) an environment-responsive agent that is capable of transporting out of the composition or facilitates out-transport of one or more beneficial agents from the composition after the composition is applied to a subject. L'invention concerne des compositions qui contiennent un agent volatil et qui peuvent être utilisées pour créer un film mince sur la peau d'un sujet, l'agent volatil pouvant être transporté hors du film. Dans un mode de réalisation, l'agent volatil est transporté hors de la composition par convection. Dans un mode de réalisation, l'agent volatil est transporté hors de la composition par diffusion. L'invention concerne également une composition destinée à être appliquée sur la peau d'un sujet, la composition comprenant a) un polymère d'organopolysiloxane bifonctionnel ayant un groupe insaturé et un groupe hydrure; et b) un agent sensible à l'environnement qui peut transporter la composition ou faciliter le transport vers l'extérieur d'un ou de plusieurs agents bénéfiques à partir de la composition après l'application de la composition à un sujet.